Determinants of Satisfaction with an Urban Tourism Destination: The Case of Barcelona - Garín-Muñoz, Teresa; J. Moral, María (Journal of Reviews on Global Economics, 2017)
Conscious of the central role of satisfaction in the success of a destination we examine the relationship between a destination’s attributes and overall satisfaction. Based on the information about 19 destination attributes and using a principal factor analysis, we identified 5 relevant dimensions, with â€œAccommodation and restaurant servicesâ€ as the key factor to explain overall satisfaction. Next, we explore the potential moderating effects of tourist and trip characteristics on that relationship. Our results suggest that the estimated relationship is very stable across types of tourists, trip features or purpose of travel. We use a survey of 2,484 interviews conducted with international tourists that visited Barcelona throughout 2013. Empirical findings allow an efficient allocation of resources in order to achieve maximum satisfaction. Therefore, they are useful to help policy makers and entrepreneurs select targets for promotion, and attain high destination competitiveness.